Molecular markers for differentiating the populations of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), vector of begomoviruses - and V.V. RAMAMURTHY*, S. JAYASEKERA, V.G. MALATHI (Indian Phytopathology, 2008)
Application of molecular markers for differentiating populations of whitefly, the vector of begomoviruses is gaining importance. In this study, hundred and four random primers were used to analyze variations, if any, among the four populations of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). RAPD profiles were generated for the genome DNA of B. tabaci adults obtained from the research farms of the Indian Agricultural Research Institute, New Delhi from four host species, brinjal, cotton, okra and soybean. The Operon primer A13 amplified the DNA from three populations (brinjal, cotton and soybean), while the primers F2, F12, H9 and H16 differentiated all the four populations. These primers were identified as important molecular markers since it gave good indications of polymorphism, existing among the four populations.